Effects of refuge availability on growth and survival of YOY Arctic char (Salvelinus alpinus) - Nilsson, Per (2006)
Risk of predation induces behavioural responses in prey, such as decreased activity and avoidance of risky habitats. Sheltering by prey in low risk habitat not only constrains the physical area but also the accessibility of resources. Hence, variation in refuge availability affects the performance of refuging individuals. In a large scaled pond experiment I tested the effect of refuge availability on survival and growth in young-of-the-year (YOY) arctic char (Salvelinus alpinus), subject to predation from cannibalistic char. In addition, I also studied the behaviour of YOY char in response to predation risk. Results showed that predation decreased both survival and growth of YOY char. Increasing refuge availability decreased the mortality of YOY char, but had no effect on growth. Risk of predation restricted the habitat use of YOY char to the protected near shore habitat. There was also a density dependent resource depletion in the refuge habitat when cannibals were present, induced by refuge availability and habitat use of YOY char. The overall results suggest predation to be the key factor limiting growth and survival in YOY char rather than resource competition, and that both quality and density of refuges affect the survival of YOY char.